Preclinical and clinical characterization of the RORγt inhibitor JNJ-61803534 - Xiaohua Xue (Nature Portfolio, 2021)
Abstract The nuclear receptor retinoid-related orphan receptor gamma t (RORγt) plays a critical role in driving Th17 cell differentiation and expansion, as well as IL-17 production in innate and adaptive immune cells. The IL-23/IL-17 axis is implicated in several autoimmune and inflammatory diseases, and biologics targeting IL-23 and IL-17 have shown significant clinical efficacy in treating psoriasis and psoriatic arthritis. JNJ-61803534 is a potent RORγt inverse agonist, selectively inhibiting RORγt-driven transcription versus closely-related family members, RORα and RORβ. JNJ-61803534 inhibited IL-17A production in human CD4+ T cells under Th17 differentiation conditions, but did not inhibit IFNγ production under Th1 differentiation conditions, and had no impact on in vitro differentiation of regulatory T cells (Treg), nor on the suppressive activity of natural Tregs. In the mouse collagen-induced arthritis model, JNJ-61803534 dose-dependently attenuated inflammation, achieving ~ 90% maximum inhibition of clinical score. JNJ-61803534 significantly inhibited disease score in the imiquimod-induced mouse skin inflammation model, and dose-dependently inhibited the expression of RORγt-regulated genes, including IL-17A, IL-17F, IL-22 and IL-23R. Preclinical 1-month toxicity studies in rats and dogs identified doses that were well tolerated supporting progression into first-in-human studies. An oral formulation of JNJ-61803534 was studied in a phase 1 randomized double-blind study in healthy human volunteers to assess safety, pharmacokinetics, and pharmacodynamics. The compound was well tolerated in single ascending doses (SAD) up to 200 mg, and exhibited dose-dependent increases in exposure upon oral dosing, with a plasma half-life of 164 to 170 h. In addition, dose-dependent inhibition of ex vivo stimulated IL-17A production in whole blood was observed, demonstrating in vivo target engagement. In conclusion, JNJ-61803534 is a potent and selective RORγt inhibitor that exhibited acceptable preclinical safety and efficacy, as well as an acceptable safety profile in a healthy volunteer SAD study, with clear evidence of a pharmacodynamic effect in humans.